2012
DOI: 10.4070/kcj.2012.42.8.558
|View full text |Cite
|
Sign up to set email alerts
|

Rupture and Spontaneous Sealing of a Coronary Aneurysm After Deployment of Drug-Eluting Stent

Abstract: Lesions with coronary artery aneurysm (CAA) can become complicated during percutaneous coronary intervention. Here, we report a case of a 78-year-old man who developed a rupture, and spontaneous sealing of the CAA occurred after stent implantation, as shown by computed tomography coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Kwon et al [11] described a case in which an acute stent thrombosis (patient taking dual antiplatelet therapy) was a consequence of aneurysm thrombosis involved in a lesion treated with a DES. The authors observed a hematoma in the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al [11] described a case in which an acute stent thrombosis (patient taking dual antiplatelet therapy) was a consequence of aneurysm thrombosis involved in a lesion treated with a DES. The authors observed a hematoma in the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…Etiyolojik faktörlere bakıldığında en sık etken ateroskleroz olup diğer sebepler arasında Kawasaki hastalığı, otoimmün hastalıklar, travma ve enfeksiyon sayılabilir (4,5) . Girişimsel kardiyolojinin artmasıyla birlikte işlem sonrası koroner anevrizma görülme sıklığı artmıştır (6,7) . Koroner arter anevrizması bulunan birçok olgu asemptomatik olup, semptomlar arasında miyokart enfarktüsü, tamponad, süperiyor vena kava sendromu, sağ ventrikül çıkış yolunun obstrüksiyonu, kalp yetmezliği ve ani ölüm sayılabilir (8)(9)(10) .…”
Section: Discussionunclassified